Factors that influence job satisfaction among employees in Majlis Perbandaran Alor Gajah / Effa Filzah Mahadi - Mahadi, Effa Filzah (Faculty of Business and Management, 2020)
The purpose of study is to identify the factors that influence job satisfaction among employees in Majlis Perbandaran Alor Gajah. A conceptual framework comprises of job satisfaction as dependent variable and three factors which are environmental factors, intrinsic rewards and extrinsic rewards as independent variables. A total of 144 questionnaires were answered and were found usable. The collected data was analyse using Statistical Package for Social Science Version 22 (SPSS V22). The analyses employed to analyse the obtained data were frequencies distribution analysis, descriptive analysis, reliability analysis, Pearson correlation analysis and multiple regression analysis. The result revealed that environmental factors and intrinsic rewards have significant and positive impact on employee job satisfaction. Meanwhile, for the extrinsic rewards has no significant relationship with job satisfaction. Result also showed that intrinsic reward impacted job satisfaction the most. Therefore, the organization should take into consideration, in selecting intrinsic rewards based on employees’ performance in order to enhance the level satisfaction among employees in organization.